2019
DOI: 10.18584/iipj.2019.10.3.8322
|View full text |Cite
|
Sign up to set email alerts
|

Police Stops and Searches of Indigenous People in Minneapolis: The Roles of Race, Place, and Gender

Abstract: We examine disparities in police stops, searches, and arrests of Native Americans in Minneapolis, a major metropolitan area with a substantial Native American population. During the study period, 1.42% of women in Minneapolis reported their race as American Indian or Alaska Native, but the Minneapolis police reported that 6.43% of police stops of women (including vehicle stops and non-vehicle stops) involved Native Americans. Native American men comprise 1.51% of the male population and 3.29% of police stops o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…At the center of this conversation lies the relationship between police and race‐class subjugated (RCS) communities (Soss & Weaver, 2017). Spanning place and methodological approaches, researchers consistently find that poor Black, Latinx, and Native communities disproportionately experience both over‐policing–including aggressive police presence, frequent harassment, enforcement of low‐level offenses–and under‐protection, including failure to prevent interpersonal and community disorder and violence (Bell, 2017; Boyles, 2019; Gorsuch & Rho, 2019; Rios, 2011). Meares (1997) argues that this paradox of over‐policing and under‐protection produces “dual frustration,” leaving communities burdened by both community and police violence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the center of this conversation lies the relationship between police and race‐class subjugated (RCS) communities (Soss & Weaver, 2017). Spanning place and methodological approaches, researchers consistently find that poor Black, Latinx, and Native communities disproportionately experience both over‐policing–including aggressive police presence, frequent harassment, enforcement of low‐level offenses–and under‐protection, including failure to prevent interpersonal and community disorder and violence (Bell, 2017; Boyles, 2019; Gorsuch & Rho, 2019; Rios, 2011). Meares (1997) argues that this paradox of over‐policing and under‐protection produces “dual frustration,” leaving communities burdened by both community and police violence.…”
Section: Introductionmentioning
confidence: 99%
“…Yet few sociolegal studies explore the experiences of women with law enforcement and legal socialization (for exceptions see Elliott & Reid, 2019; Malone Gonzalez�2019). Even fewer studies examine how women across other racial identities, including white women, in heavily policed neighborhoods perceive and interact with police (though see Cobbina, 2019; Gorsuch & Rho, 2019; Hitchens et al, 2018). Bridging sociolegal and criminological scholarship with intersectional feminist theory, we examine women's experiences of dual frustration through the lens of gendered racial vulnerability (Malone Gonzalez�2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important given that communities may interface differently with police. Patients of Black, Latinx, and Indigenous descent are significantly more likely to have had prior harmful experiences with law enforcement, which may cultivate a lack of trust in both law enforcement and the healthcare system 28,30–35 . Two studies in our review found that some patients described police being aggressive to them in seeking information, failing to consider their wellbeing, and experiencing new distress with police presence 26,27 .…”
Section: Discussionmentioning
confidence: 93%
“…Patients of Black, Latinx, and Indigenous descent are significantly more likely to have had prior harmful experiences with law enforcement, which may cultivate a lack of trust in both law enforcement and the healthcare system. 28,[30][31][32][33][34][35] Two studies in our review found that some patients described police being aggressive to them in seeking information, failing to consider their wellbeing, and experiencing new distress with police presence. 26,27 We found no other examinations of patient experiences of police following traumatic injury, along with no rigorous research to evaluate if current police practices contribute to disparities in transport times.…”
Section: Discussionmentioning
confidence: 99%